The Reform of the Parliamentary Threshold System Based on Human Rights: Evidence from the United States - Putra Perbawa , I Ketut Sukawati Lanang; Kusumaningtyas , Reza Octavia; Jailani, Abdul Kadir (Faculty of Law, Universitas Slamet Riyadi, 2022)
Using thresholds in elections facilitates fair competition among political parties for votes. Nevertheless, this threshold rule could pose a legal obstacle if a political party fails to get a parliamentary seat in an election due to insufficient voter support. This research intends to assess the ongoing significance of the parliamentary threshold system in Indonesia through comparison studies with other nations. This inquiry employs a normative juridical methodology. The research findings indicate that implementing the Parliamentary Threshold should better accommodate each region's unique and varied political objectives. This challenges the notion of variety within unity, potentially hindering the progress of political goals at both regional and national scales. National parliamentary thresholds can limit or remove regional political rights. Furthermore, the United States, which originated the presidential system of government, possesses the most extensive federal constitution worldwide. The United States spearheaded this progress by integrating human rights into its constitution. The United States operates under a two-party system and does not employ a specific legislative threshold system. Elections are conducted at several levels of government, including federal, state, and municipal. However, there are no established uniform criteria for parties or candidates to meet to be eligible for representation. The electoral college method also impacts the allocation of ballots, enhancing the probability of participation and involvement from each political party. Political parties experience more excellent stability. Therefore, Indonesia should adopt additional inclusive reforms based on human rights principles to establish specific benchmarks.